Penegakan Hukum Terhadap Tindak Pidana Pencurian yang Dilakukan oleh Anak di Kota Semarang (Studi Putusan Nomor : 2/Pid.Sus-Anak/2023/Pn Smg) - WIilliam Aditama, Calvin; Faozi, Safik (Universitas Ekasakti, 2024)
The phenomenon of juvenile delinquency, or child crime, is currently frequently encountered, especially crimes that harm society or other people, such as criminal acts of theft committed by children. The purpose of this research is to determine the factors that influence children in committing a crime of theft and to analyze the decision of the Semarang District Court judge No: 2/Pid.Sus-Anak/2023/PN Smg in the crime of theft committed by a child. The method used in this research is the Normative Juridical Method, the specifications used are Analytical Descriptive, and the method used in this research is Literature Study. The influencing factors are caused by heredity and environmental factors. Congenital or hereditary factors are the first factor that influences a child's growth and development. This factor can be interpreted as all individual traits or characteristics that are inherited from children or all the physical and psychological potential that a person has from the time of conception as an inheritance from parents. Based on the provisions of Article 5 paragraph 1 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, in resolving juvenile cases through the Juvenile Criminal Justice System, it is mandatory to prioritize a restorative justice approach.